Sinusoidal Three-Phase Windings of Electric Machines - Buksnaitis, Jonas Juozas (Springer International Publishing : Imprint: Springer, 2016)
This book presents a thorough analysis of newly available sinusoidal three-phase windings in electrical machines, which provide many benefits over traditional windings, including energy savings, noise and vibration reduction, and reduced need for non-ferrous metals. The author's instruction on the implementation of this innovative optimization will be quite useful to researchers, developers and producers of electrical machines, as well as students mastering electromechanics.